EFFECT OF DIETARY FRESH AZOLLA INCLUSION ON CARCASS TRAITS OF WHITE PEKIN BROILER DUCKS (Indian Journal of Animal Production and Management, 2016)
This study was undertaken to investigate the effect of inclusion of dietary fresh Azolla in the basal diet of  white pekin broiler ducks on carcass traits. Three dietary treatments were given such as G1: Basal diet, G2:  Basal diet + 5% Fresh Azolla of basal diet, G3: Basal diet + 10% Fresh Azolla of basal diet. Parameters  such as dressing (%), eviscerated yield (%), giblet (%), neck (%), wing (%), breast (%), thigh (%), drumstick  (%) were recorded. Significant difference was recorded (P≤0.05) between the groups for giblet yield, while  no significant difference could be noticed for any other traits.
Keywords: Azolla; Carcass traits; White pekin broiler ducks